2007
DOI: 10.1523/jneurosci.0815-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular Glutamate Transporter 1 Is Required for Photoreceptor Synaptic Signaling But Not For Intrinsic Visual Functions

Abstract: Glutamatergic neurotransmission requires vesicular glutamate transporters (VGLUTs) to sequester glutamate into synaptic vesicles. Generally, VGLUT1 and VGLUT2 isoforms show complementary expression in the CNS and retina. However, little is known about whether isoform-specific expression serves distinct pathways and physiological functions. Here, by examining visual functions in VGLUT1-null mice, we demonstrate that visual signaling from photoreceptors to retinal output neurons requires VGLUT1. However, photoen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 43 publications
2
49
0
Order By: Relevance
“…Figure 3B shows the mixture of NBQX, AP5, AP4, and DHβE (middle trace) (11,30) effectively blocks the short latency photoreceptordriven responses in RGCs recorded from a P16 WT mouse (top trace). This same mixture of synaptic blockers failed to block the light-driven ipRGC responses in a P8 WT mouse (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 3B shows the mixture of NBQX, AP5, AP4, and DHβE (middle trace) (11,30) effectively blocks the short latency photoreceptordriven responses in RGCs recorded from a P16 WT mouse (top trace). This same mixture of synaptic blockers failed to block the light-driven ipRGC responses in a P8 WT mouse (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Physiologically, in mouse retina, melanopsin-expressing ipRGCs can be activated by light as early as the day of birth (9,10). Concomitantly, by postnatal day 1 (P1), ipRGCs express vesicular glutamate transporter type 2, necessary for the synaptic release of glutamate from ipRGCs (11), and project their axons to the suprachiasmatic nucleus (SCN) of the hypothalamus (12). Furthermore, the retina-SCN tract in rats can be activated by light immediately after birth (9,10,13).…”
mentioning
confidence: 99%
“…AG208) eliminates immunostaining (manufacturer's worksheet). No immunostaining was observed when this antibody was used on VGLUT1 knockout mouse retina (Johnson et al, 2007).…”
Section: Antibody Characterizationmentioning
confidence: 96%
“…RGCs sending axon collaterals into the IPL have been described in cat (Dacey 1985), monkey (Usai et al 1991) and human retina (Peterson and Dacey 1998); in human retina ~2% the RGCs examined had intraretinal axon collaterals that terminated in the outer half of the IPL and arose from RGCs with sparsely branched monostratified dendritic trees that aborized in the ON sublayer of the IPL (Peterson and Dacey 1998). In the cat retina, a small number of varicose processes in the IPL stain for one of the isoforms of the vesicular glutamate transporter (VGLUT2) and it was suggested that these may represent RGC axon collaterals (Fyk-Kolodziej et al 2004); ipRGCs use glutamate as a neurotransmitter and express VGLUT2 (Johnson et al 2007;Engelund et al 2010). A preliminary report indicates that indeed some ipRGCs may send axon collaterals into the IPL (Joo et al 2011).…”
Section: Iprgcs Provide Excitatory Drive To Dopaminergic Amacrine Cellsmentioning
confidence: 99%